Google Sheets-Based Accounting System as a Financial Management Solution for Mikaba's Shop - Nurul Qomariyah; Ade Gunawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy by creating jobs, providing goods and services, and supporting local innovation. Despite this, many MSMEs still face difficulties in financial management, especially in transaction recording and reporting. Kedai Mikaba, a culinary MSME in Pekalongan, encountered challenges due to the absence of a structured bookkeeping system. Transactions were noted manually and often incompletely, making it difficult to monitor cash flow, prepare profit and loss statements, and make informed business decisions. This community service project aimed to design and implement an accounting system using Google Sheets as a practical, low-cost, and adaptive solution. The method applied was Participatory Action Research (PAR), which actively involved the business owner in observation, interviews, system design, training, and implementation. Results showed clear improvements in transparency, accuracy, and consistency of financial records. The owner is now able to record daily transactions, view recaps in real time, and generate automatic profit and loss reports. This process not only simplified financial management but also raised awareness of systematic bookkeeping as a foundation for sustainability. Google Sheets thus demonstrates potential as an effective tool for MSMEs, while future development may focus on mobile-based applications for greater accessibility.